Indigenous peoples, identity, history, and law: the United States and Australian experience - J. Wunder (Law Text Culture, 1998)
Approximately 350 million people in the world, or roughly 6% of the world's population are indigenous. Significantly diverse, Native peoples live in at least 72 countries as nations within nations (Echo-Hawk 1997: 1_2). Indigenous peoples existed before colonists arrived in their homelands, and yet the conquerors have consistently sought to develop legal standards of indigenous identity. In every instance, identity is related to land rights, cultural freedoms, and sovereignty issues. What is an indigenous person's legal identity? A people's identity? How is it determined? Who determines it? Such simple questions have so often generated complex and confusing answers.